Pengaruh Metode Two Stay Two Stray Terhadap Karakter Disiplin Siswa Pada Mata Pelajaran Akidah Akhlak Di MI Tarbiyatul Atfhal - Dwi Indah Lestari; Maemunah Sa'diyah; Kamalludin Kamalludin (LPPM Universitas Ibn Khaldun, Bogor, 2020)
AbstractThe purpose of this study is to determine whether or not there is an influence of the use of the two stay two stray (TSTS) method to the discipline character of students at MI Tarbiyatul Atfhal. The method used is experimental research. The sample of this study included 30 control class students and 30 experimental class students. Research instruments in the form of observation, tests, and documentation. The results of the study were calculated using SPSS 20 to determine the level of influence of the learning method. The results of this study are the influence of the Two Stay Two Stray method on the character of student discipline in the subjects of the Islamic Morals in the experimental and control classes in class V MI Tarbiyatul Athfal ie there are differences in the average of the two classes with the average value of the pre-control class test 47.2 and post-test 71.2. While the experimental class got an average score of 49.07 pre-test and 86.67 post-test. Then it can be concluded that the two stay two stray method has an influence on the character of student discipline at MI Tarbiyatul Atfhal. Keywords: Disciplinary Character, Learning Method, Two Stay Two Stray.